Protective Effects of Ellagic Acid Against Alcoholic Liver Disease in Mice - Zhao, Liang; Mehmood, Arshad; Soliman, Mohamed Mohamed; Iftikhar, Asra; Iftikhar, Maryam; Aboelenin, Salama Mostafa; Wang, Chengtao (Frontiers in Nutrition, 2021)
Ellagic acid, a natural polyphenolic compound commonly present in vegetables, fruits, nuts, and other edible plants, exerts many pharmacological activities. The present project was designed to explore the hepatoprotective effect of ellagic acid against alcohol-induced liver disease (ALD) and the correlation among alcohol, oxidative stress, inflammation, and gut microbiota. 50% (v/v) alcohol (10 mL/kg bw daily) was orally administrated for 4 weeks in mice along with ellagic acid (50 and 100 mg/kg bw). Alcohol administration significantly (p < 0.05) increased activities of alanine aminotransferase (ALT) and serum aspartate aminotransferase (AST), levels of triglyceride (TG), low density lipoprotein (LDL), free fatty acid (FFA) and total cholesterol (TC), and decreased contents of the high-density lipoprotein (HDL) in model group compared to control group, which were further improved by ellagic acid (50 or 100 mg/kg bw). Furthermore, daily supplementation of ellagic acid alleviated hepatic antioxidant activities (GSH-Px, CAT, MDA, SOD, and GSH), pro-inflammatory cytokines levels (IL-6, IL-1β, and TNF-α), genes expressions (Tlr4, Myd88, Cd14, Cox2, Nos2, and Nfκb1), and histopathological features in alcohol-induced liver injury mice. Additionally, results also revealed that ellagic acid supplementation improved alcohol-induced gut microbiota dysbiosis. In conclusion, ellagic acid mitigated oxidative stress, inflammatory response, steatosis, and gut microbiota dysbiosis in ALD mice. Our results suggested that ellagic acid could be applied as an ideal dietary therapy against ALD.